The impact of the COVID-19 pandemic on further learning in Vocational Education : analysis and best practices - Victorovna Lomovtseva, Natalya [Verfasser] (My University, 2022)
"The College of Electric Power and Mechanical Engineering (CEM) is part of the structure of the Institute of Engineering-Pedagogical Education of the Russian State Vocation Pedagogical University (RSVPU). The College carries out educational activities based on educational programmes of intermediate Vocational Education. Adapting to the new reality showed that bite-size learning can be called one of the most successful approaches to solve the problem of students’ scattered attention. Virtual/augmented reality and immersive technologies have become a powerful and promising tool in education thanks to their unique technological characteristics that distinguish them from other IT applications. However, the forced transition to a distance mode of operation was a serious challenge for all participants in the educational process and was associated with great difficulties for the administration of the institutions and for teachers as well as for students." (Author's abstract ; BIBB-Doku)
Keywords: L 4.2.3 Internetbasiertes Lernen / E-Learning; L 4 Medien & Technologien; 370; Berufsbildung; Pandemie; E-Learning; Augmented Reality; virtuelle Realität; Russland